OP0090 EFFICACY OF SUBCUTANEOUS TANEZUMAB FOR THE TREATMENT OF CHRONIC LOW BACK PAIN: AN ANALYSIS OF BRIEF PAIN INVENTORY-SHORT FORM SCORES FROM A 56-WEEK, RANDOMIZED, PLACEBO- AND TRAMADOL-CONTROLLED, PHASE 3 TRIAL. (2nd June 2020) - Markman, J.; Perrot, S.; Ohtori, S.; Schnitzer, T.; Beydoun, S.; Viktrup, L.; Yang, R.; Bramson, C.; West, C.; Verburg, K.
Abstract : Background: Tanezumab, a monoclonal antibody against nerve growth factor, was recently evaluated in an 80 week placebo and tramadol-controlled trial in patients with chronic low back pain (CLBP) and a history of inadequate response to standard-of-care analgesics (NSAIDs, opioids, etc). Primary endpoint was change in Low Back Pain Intensity (LBPI) at week 16 vs placebo. Key secondary endpoints were the proportion of patients with ≥50% improvement in LBPI at week 16, change in Roland Morris Disability Questionnaire score at week 16, and change in LBPI at week 2 (all vs placebo). Tanezumab 10mg met the primary and all key secondary endpoints. Tanezumab 5mg did not meet the primary endpoint, but improved 2 of 3 key secondary endpoints. Due to the primary endpoint result and the statistical gate-keeping approach to control for multiple comparisons, a conclusion of superiority over placebo could not be made for the 5mg dose. Objectives: To further characterize tanezumab's effects on pain and function in this trial through analysis of Brief Pain Inventory-short form (BPI-sf) scores. Methods: Patients received placebo (n=406), subcutaneous (SC) tanezumab 5mg (every 8 weeks; n=407), SC tanezumab 10mg (every 8 weeks; n=407) or oral tramadol prolonged-release (100-300mg/day; n=605). Pre-specified secondary endpoints included BPI-sf worst pain, average pain, the overall pain interference index, and selected individual domains of the index (general activity, walking ability, sleep, and normal work). Least squares (LS) mean (standard error [SE]) changes from baseline in BPI-sf scores were compared between groups (unadjusted for multiplicity) at week 16 using an analysis of covariance model. Scores range from 0-10 with higher scores indicating greater pain severity or functional impairment. Results: LS mean (SE) differences from placebo for worst pain were -0.52 (0.19) for tanezumab 5mg (p≤0.01), -0.54 (0.19) for tanezumab 10mg (≤0.01), and -0.24 (0.17) for tramadol (p=0.17). LS mean (SE) differences from placebo for average pain were -0.37 (0.18) for tanezumab 5mg (p=0.04), -0.46 (0.18) for tanezumab 10mg (≤0.01), and -0.17 (0.16) for tramadol (p=0.29). LS mean (SE) differences from placebo for the pain interference index were -0.41 (0.18) for tanezumab 5mg (p=0.03), -0.58 (0.18) for tanezumab 10mg (≤0.01), and -0.15 (0.17) for tramadol (p=0.39). Effects of tanezumab were not statistically different (p>0.05) from tramadol for worst pain, average pain, and the pain interference index, with exception of the pain interference index for tanezumab 10mg (p=0.01). Mean dose of tramadol was 203mg/day at week 16. Tanezumab 10mg significantly (p<0.05) improved individual domains of the pain interference index (general activity, walking ability, sleep, and normal work) vs placebo and vs tramadol. Tanezumab 5mg significantly (p<0.05) improved pain interference with general activity and normal work vs placebo, and sleep vs placebo and vs tramadol. No statistical differences in any domain was observed for tramadol vs placebo. Conclusion: Tanezumab 5mg and 10mg significantly improved worst pain, average pain, and overall pain interference index scores vs placebo in patients with CLBP. Tanezumab 10mg also significantly improved the overall pain interference index vs tramadol. Tanezumab 5mg significantly improved most individual domains of the pain interference index vs placebo, while tanezumab 10mg significantly improved all domains assessed vs placebo and vs tramadol. Disclosure of Interests: John Markman Consultant of: Consultant: Trigemina, Editas Medicine, and Plasma Surgical; Advisory board: Clexio Biosciences, Flexion Therapeutics, Quark Pharmaceuticals, Quartet Medicine, Collegium Pharmaceutical, Purdue Pharma, Biogen, Novartis, Aptinyx, Nektar, Allergan, Grünenthal, Eli Lilly and Company, Depomed, Janssen Pharmaceuticals, Teva Pharmaceutical Industries, KemPharm, Abbott Laboratories, Plasma Surgical, Chromocell, Convergence Pharmaceuticals, Inspirion, Pfizer, Sanofi, Daiichi Sankyo, and Trevena; Data safety monitoring boards for Novartis and Allergan, Serge Perrot Consultant of: Grunenthal, Pfizer, Lilly, MSD, Sanofi, Menarini, Seiji Ohtori: None declared, Thomas Schnitzer Consultant of: Pfizer, Lilly, AstraZeneca, GSK, Said Beydoun Grant/research support from: Argenx, Catalyst Pharma, Mallinckrodt, Pfizer, UCB, Consultant of: Alexion, Akcea, Alnylam, CSL, Takeda, Mitsubishi Tanabe, Speakers bureau: Alexion, Akcea, Alnylam, CSL, Takeda, Mitsubishi Tanabe, Lars Viktrup Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Ruoyong Yang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Candace Bramson Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Christine West Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Ken Verburg Shareholder of: Pfizer Inc, Employee of: Pfizer Inc